PENGARUH CUSTOMER SATISFACTION, BRAND IMAGE, DAN DIGITAL MARKETING TERHADAP BRAND LOYALTY DI KALANGAN MAHASISWA PENGGUNA PRODUK GLAD2GLOW DI KOTA YOGYAKARTA - Harfianti Harfianti; Eko Prasojo (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the influence of customer satisfaction, brand image, and digital marketing on brand loyalty among college students using Glad2Glow products in Yogyakarta. This study employed quantitative research. The population was college students using Glad2Glow products in Yogyakarta. The sample size was 373 respondents. The sampling technique used was purposive sampling, a method based on the researcher's judgment, and then processed using SPSS. Data collection used a questionnaire. Instrument testing techniques used validity and reliability. Data analysis techniques used descriptive analysis, classical assumptions, multiple linear regression, the coefficient of determination, and hypothesis testing.The results showed that the Customer Satisfaction variable had a t-value of 3.044 with a significance level of 0.002, indicating that customer satisfaction significantly influences brand loyalty. Furthermore, Brand Image showed a very significant influence on brand loyalty, with a t-value of 11.582 and a significance level of 0.000. Similarly, the Digital Marketing variable has a t-value of 4.774 and a significance value of 0.000, which also indicates a significant influence on Brand Loyalty. The F-value obtained is 346.630 with a significance value of 0.000. Because the significance value is less than 0.05, the regression model used is declared statistically significant. This confirms that the variables Customer Satisfaction, Brand Image, and Digital Marketing simultaneously have a significant influence on Brand Loyalty.